Improving Students' Science Knowledge Competence through the Implementation of Index Card Match Type of Cooperative Learning Model - Made Inten Surya Devi Surya; Ida Bagus Gede Surya Abadi; Anak Agung Gede Agung (Jurnal Ilmiah Sekolah Dasar, 2022)
The less optimal use of models causes the low competence of students' science knowledge during learning, so students find it challenging to understand learning. This study aims to analyze the Index Card Match Type Cooperative Learning Model for the science knowledge competence of class students. This research is a quasi-experimental study with a non-equivalent control group design. The population is all of the fifth grades of elementary school, comprising 15 classes with a total of 463 students. The sample was determined using the cluster random sampling technique. In data collection, the instrument used was an ordinary multiple-choice objective test to obtain data in the form of scientific knowledge competency scores in the form of quantitative data. The GSn results were analyzed using t-test analysis. The mean score of the GSn science knowledge competency in the experimental group was 22.96, and that of the control group was 17.46. The results of the data analysis proved that there were significant differences between the experimental group and the control group. Applying the Index Card Match Type Cooperative Learning model can increase students' science knowledge competence. So it was concluded that the Index Card Match Type Cooperative Learning model affected the science knowledge competence of class V SD.